Effector T Helper Cells Are Selectively Controlled During Pregnancy and Related to a Postpartum Relapse in Multiple Sclerosis - Koetzier, Steven C.; Neuteboom, Rinze F.; Wierenga-Wolf, Annet F.; Melief, Marie-José; de Mol, C. Louk; van Rijswijk, Angelique; Dik, Willem A.; Broux, Bieke; van der Wal, Ronald; van den Berg, Sjoerd A. A.; Smolders, Joost; van Luijn, Marvin M. (Frontiers in Immunology, 2021)
Background: Multiple sclerosis (MS) patients are protected from relapses during pregnancy and have an increased relapse risk after delivery. It is unknown how pregnancy controls disease-contributing CD4+ T helper (Th) cells and whether this differs in MS patients who experience a postpartum relapse. Here, we studied the effector phenotype of Th cells in relation to pregnancy and postpartum relapse occurrence in MS. Methods: Memory skewing and activation of effector Th subsets were analyzed in paired third trimester and postpartum blood of 19 MS patients with and without a postpartum relapse and 12 healthy controls. Ex vivo results were associated with circulating levels of pregnancy-induced hormones and mirrored in vitro by exposing proliferating Th cells to corresponding serum samples. Results: Based on HSNE-guided analyses, we found that effector memory proportions of Th cells were increased in postpartum versus third trimester samples from MS patients without a postpartum relapse. This was not seen for relapsing patients or healthy controls. CXCR3 was upregulated on postpartum memory Th cells, except for relapsing patients. These changes were verified by adding sera from the same individuals to proliferating Th cells, but did not associate with third trimester cortisol, estradiol or progesterone levels. For relapsing patients, activated memory Th cells of both third trimester and postpartum samples produced higher levels of pro-inflammatory cytokines. Conclusion: Effector Th cells are differentially regulated during pregnancy in MS patients, likely via serum-related factors beyond the studied hormones. The pro-inflammatory state of memory Th cells during pregnancy may predict a postpartum relapse.